REPRESENTASI FEMINISME DALAM FILM SITI - M. Rezha Alfauzi; Nita Rimayanti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Women position in society more often seen as a graceful, loving and emotional figure, weak, and on some society embedded a concept that women was an object, not as an subject as like as men. Until now still many region that despise at women and assume degree of women not equal to men, just like some society with patriarki cultures, women positioned as housekeeper, they are not allowed to work outside of the home. With this restrained condition without space to grow up, its hard for women to enlarge their knowledge and their talent. Women’s struggle to gain their rights and from sex discrimination known as feminism. Feminism was women effort and struggle to refused to be subordinate and be degraded by dominant culture for in terms of politic, economic, social, or cultural side. This research using Roland Barthes semiotic analysis that review meaning of denotation, meaning of conotation, and myth from film. Purpose of this research is to know denotation meaning of feminism, conotation meaning of feminism, and myth in the film Siti.Methode used in this research is qualitative deskriptive with Roland Barthes semiotic analysis. Data collection using documentation, obsevation, and study of literature. This research located at Pekanbaru. Dana analysis technique using Roland Barthes Semiotic that examine meaning.Result of this research shown meaning of denotation, meaning of conotation, and semiotic myth from the film Siti. Denotation meaning seen from this film clearly shows feminism thought which women can change perception of society, its indicated from dialogue, women character behavior from this film tell that women are also strong and independent being. Meaning of conotation seen by Siti behavior from smoking and drinking alcohol, tell that women are also free to do whatever they want, they also can make decisions with their minds and not depent on men. Semiotic myth in society as well as women that often go out at night is naughty women, or else women must obey to their husband, should not argue anything said by their husband. Also ideology by society with east culture like Indonesia, always assume that women position behind men position. This film dismissed myth and ideology and perception that long-established inside those society. Women with feminism thought in the film shown with strong character, independent, and have freedom for their own mind and body.Keyword : representation, feminsm, semiotic